Midwifery education in New Zealand: Education, practice and autonomy. (February 2016) - Gilkison, Andrea; Pairman, Sally; McAra-Couper, Judith; Kensington, Mary; James, Liz
Abstract: New Zealand's midwifery education model is intertwined with a practice model which is underpinned by autonomy and partnership. The curriculum prepares students for practice across the scope of midwifery on their own responsibility. While students have formal learning opportunities within educational institutions they spend at least half of their programme learning through authentic work experiences alongside midwives and women. Midwifery educators partner with practising midwives to support students to develop the knowledge, skills and attitudes required to practise midwifery in the New Zealand context. This paper provides an overview of New Zealand's midwifery education model and identifies how it is integrated with New Zealand's unique midwifery service.